Directing the Deformation Paths of Soft Metamaterials with Prescribed Asymmetric Units. (23rd March 2015) - Wu, Gaoxiang; Cho, Yigil; Choi, In‐Suk; Ge, Dengteng; Li, Ju; Han, Heung Nam; Lubensky, Tom; Yang, Shu
<x xml:space="preserve">Abstract</x> By prescribing asymmetric ligaments with different arrangements in elastomeric porous membranes of pre‐twisted kagome lattices, the buckling instability is avoided, allowing for smooth and homogenous structural reconfiguration in a deterministic fashion. The stress–strain behaviors and negative Poisson's ratios can be tuned by the pre‐twisting angles.